ORIENTASI PEMAHAMAN MATAHARI SEBAGAI SUMBER ENERGI DALAM PERSPEKTIF SAIN DAN AL-QUR’AN DI SMP ALDEPOS BOARDING SCHOOL BOGOR - Badru Tamam; Asep Muksin; M. Suaib Tahir; Mahmud Salim; Winona Lutfiah; Mulyani Mulyani (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
This research tries to examine the signs of the Qur'an related to the sun as one of Allah's creations. which is the source of energy for life. This study describes that the Qur'an hints at the sun with the words sirâj and dhiyâ', both of which mean that sunlight comes from itself. The method used in this study is a qualitative analysis method through library research with an interpretative descriptive approach. The temporary conclusion of this study shows that based on the cues in the Qur'an, it shows that the Qur'an and Science explain that the sun has a function as a source of light which not only illuminates but can provide and produce heat or energy which is very beneficial for life. One of the benefits is as a source of light energy